Enhancing screening rates for bone health management in prostate cancer patients on androgen deprivation therapy with an automated outpatient system - Chun-Li Wang; Shian-Shiang Wang; Chuan-Shu Chen; Sheng-Chun Hung; Cheng-Che Chen; Cheng-Kuang Yang; Jian-Ri Li; Kun-Yuan Chiu; Chia-Yen Lin (Scientific Reports)
Abstract Bone health screening is crucial before and during androgen deprivation therapy (ADT) for prostate cancer, yet changes in bone mineral density during ADT are often overlooked. To improve surveillance rates, we developed an auto-recruit path integrated into the outpatient system, where a pop-up reminder prompts physicians to arrange bone health screenings when ADT is prescribed without a dual-energy x-ray absorptiometry (DXA) screening in the past year. If selected, the system orders DXA and related examinations automatically. We retrospectively reviewed DXA screening rates from 2000 to 2018. During that period, only 286 out of 3,019 patients (9.5%) received DXA screenings. After implementing the auto-recruit system, 251 out of 747 eligible patients (33.6%) were screened from March 2021 to February 2022. Participants using ADT for over a year had worse T-scores and higher osteoporosis rates (34.5% vs. 23.2%) compared to those using ADT for less than a year. Post-screening, there was a significant increase in calcium supplement and bone protective agent use, highlighting improved patient awareness and proactive bone health management. In conclusion, bone health screening for prostate cancer patients on ADT remains an unmet need. The auto-recruit path in the outpatient system effectively increases screening rates and enhances bone health management.